Job resources as intrinsic versus extrinsic motivators and the applicability of the Self-determination theory in Moroccan companies - BEZZAZ , Yasmine; MOTII, Nadia (Revue Internationale des Sciences de Gestion, 2021)
In Morocco, human resources management is evolving with the introduction of new practices by multinational groups. While past management principles relied on extrinsic rewarding and material resources to motivate employees, exploring the resources offered nowadays would help us determine the types of motivators used by Moroccan companies. We conducted semi-directed interviews with Human Resource managers in different organizational settings to gather data on motivation practices that they use within their companies. Findings suggest that both extrinsic and intrinsic motivators are valued by managers to improve their employees’ satisfaction. We were also able to support the applicability of the Self-Determination Theory in the Moroccan context through evidence of the use of a various range of motivation practices as well as the fulfillment of the three needs that are linked to intrinsic motivation, the need for autonomy, the need for competence and the need for relatedness. Many interviewees mentioned the use of non-standard work arrangements, research on these types of work settings is especially relevant in the current global circumstances. Future studies would help us examine the relationship between the different types of motivators and job satisfaction as well as health and wellbeing in the workplace.